From personification abuse to normal expression: emotional treatment for language disorders in schools - Ke, Yuguo; Zhou, Xiaozhen (Frontiers in Psychiatry, 2024)
The escalating prevalence of personification abuse in language disorders among students poses a substantial challenge for autistic students in the domain of language disorders. While prior research has mainly focused on the cognitive hurdles faced by autistic students, ongoing debates persist about the onset, severity, and roots of these challenges in their classroom behavior, with limited exploration of how preconceived notions impact personification abuse. This study aims to delve into emotional treatments for language disorders, specifically targeting personification abuse, to facilitate the shift from distorted perceptions to normative expression. It seeks to pinpoint the primary emotional interventions linked to instances of personification abuse and scrutinize the emotional factors influencing therapeutic approaches for language disorders. Methods: The research encompassed a cohort of 110 autistic students, aged 2 to 5 years, diagnosed with language disorders, all clinically determined to have autism by developmental pediatricians at a prestigious medical facility. Among these children, 95 were attending specialized schools, while 15 were situated in community settings.The outcomes disclosed that children across all developmental phases displayed instances of personification abuse in language disorders, showcasing noteworthy enhancements in personification abuse following emotional treatment. Significantly, the discernible disparity in personification abuse performance and emotional treatment can be linked to the simultaneous cognitive advancement of autistic students across four grade levels, with variations noted based on normative expressions. Discussion: These findings underscore the insufficiency of solely relying on intrinsic trends to comprehend personification abuse within an emotional treatment context. The study accentuates the potential pitfalls associated with emotional treatment for language disorders and stresses the imperative need for additional research and psychiatric intervention strategies.